Plant Aurora kinases play a role in maintenance of primary meristems and control of endoreduplication - Petrovská, Beáta; Cenklová, Věra; Pochylová, Žaneta; Kourová, Hana; Doskočilová, Anna; Plíhal, Ondřej; Binarová, Lenka; Binarová, Pavla (The New phytologist, 2012)
• The conserved family of Aurora kinases has multiple functions during mitosis. The roles of plant Aurora kinases have been characterized using inhibitor treatments. • We down-regulated Aurora kinases in Arabidopsis thaliana using RNA interference (RNAi). We carried out a detailed phenotypic analysis of Aurora RNAi plants, biochemical and microscopic studies of AtAurora1 kinase together with AtTPX2 (targeting protein for Xklp2) and γ-tubulin. • Cell division defects were observed in plants with reduced expression of Aurora kinases. Furthermore, the maintenance of primary meristems was compromised and RNAi seedlings entered endoreduplication prematurely. AtAurora1, its activator AtTPX2, and γ-tubulin were associated with microtubules in vitro; they were attached to regrowing kinetochore microtubules and colocalized on spindle microtubules and with a subset of early phragmoplast microtubules. Only the AtAurora1 kinase was translocated to the area of the cell plate. • RNAi silencing of Aurora kinases showed that, in addition to their function in regulating mitosis, the kinases are required for maintaining meristematic activity and controlling the switch from meristematic cell proliferation to differentiation and endoreduplication. The colocalization and co-fractionation of AtAurora1 with AtTPX2, and γ-tubulin on microtubules in a cell cycle-specific manner suggests that AtAurora1 kinase may function to phosphorylate substrates that are critical to the spatiotemporal regulation of acentrosomal microtubule formation and organization.
Keywords: Arabidopsis Proteins; mikrotubuly; Arabidopsis; duplikace genu; buněčné dělení; Microtubules; protein-serin-threoninkinasy; Meristem; Microtubule-Associated Proteins; proteiny huseníčku; transport proteinů; Phenotype; RNA Interference; Cell Division; kinasy Aurora; Tubulin; fenotyp; tubulin; meristém; RNA interference; Gene Duplication; proteiny asociované s mikrotubuly; Down-Regulation; down regulace; Aurora Kinases; Protein Transport; Protein Serine-Threonine Kinases